Serum Vitamin A Levels May Affect the Severity of Ocular Graft-versus-Host Disease - Tong, Jiefeng; Hu, Renjian; Zhao, Yingying; Xu, Yang; Zhao, Xiaoying; Jin, Xiuming (Frontiers in Medicine, 2017)
Allogeneic hematopoietic stem cell transplantation (HSCT) is a well-established therapeutic option for a range of inherited and acquired hematological disorders. However, graft-versus-host disease (GVHD) remains the leading cause of non-relapse mortality in allogeneic HSCT recipients. Ocular involvement occurs in up to 80% of chronic GVHD patients. In our cases, the diagnosis of vitamin A deficiency was suspected for GVHD patients. Serum vitamin A measurements were conducted to confirm clinical suspicions. Our study revealed significant decrease in serum levels of vitamin A in chronic liver GVHD patients. Although there have been many studies evaluating ocular manifestations in patients with GVHD, the present study is, to our knowledge, the first to study the relationship between vitamin A and ocular manifestations of GVHD in humans. Our data suggest that vitamin A deficiency affects the severity of ocular GVHD in adults.